Doxycycline pharmacokinetics in geese. Issue 6 (27th July 2021) - Sartini, Irene; Łebkowska‐Wieruszewska, Beata; Lisowski, Andrzej; Poapolathep, Amnart; Sitovs, Andrejs; Giorgi, Mario
Abstract: The study aims to describe the pharmacokinetics of doxycycline after a single intravenous and oral dose (20 mg/kg) in geese. In addition, two multiple‐dose simulations have been performed to investigate the predicted plasma concentration after either a 10 or 20 mg/kg daily administration repeated consecutively for 5 days. Ten geese were enrolled in a two‐phase cross‐over study with a washout period of two weeks. All animals were treated intravenously and orally with doxycycline, and blood samples were collected up to 48 h after drug administration. Sample analysis was performed using a validated HPLC‐UV method. A non‐compartmental approach was used to evaluate the pharmacokinetic parameters of the drug. A long elimination half‐life was observed (13 h). The area under the curve was statistically different between the two treatments, with the oral bioavailability being moderate (43%). The pharmacokinetic/pharmacodynamic index (%T>MIC) during the 48 h treatment period in the present study (71%) suggests that doxycycline appears to have therapeutic efficacy against some Mycoplasma species in the goose. The multiple‐dose simulations showed a low accumulation index. A dosage of 10 mg/kg/day for 5 days seemed to be adequate for a good therapeutic efficacy without reaching unnecessarily high plasma concentrations.